Fungsi tindak tutur ekspresif dalam tayangan Kick Andy-Edisi K.H. Abdurahman Wahid di channel youtube Metro TV - Lavhasa, Alfaris Cindy lavhasa; Wijayanti, Dedi; Abdi, N. Satria (Universitas Ahmad Dahlan, 2024)
A speech in a show has various types and functions. The speakers' speech in Kick Andy show is very diverse and has various functions that are interesting to study because the speech contains the value of critical and deep thinking but still wrapped in humor. This research aims to describe the function of expressive speech acts in the Kick Andy Edition of K.H. Abdurahman Wahid. This type of research is descriptive qualitative research. The subject of this research is Kick Andy Edition of K.H. Abdurahman Wahid on Metro TV Youtube Chanel. The object of this research is Expressive Speech Actions in Kick Andy Edition of K.H. Abdurahman Wahid on Metro TV Youtube Chanel. This research uses listening method in collecting data. The listening method was conducted with basic techniques in the form of tapping techniques and advanced techniques in the form of free spoken techniques (SBLC). The data analysis method uses the commensurate method with the basic technique in the form of sorting the determining elements (PUP) technique. The results of this research are as follows: (1) expressive speech act function of criticizing as much as 4 data, (2) expressive speech act function of complaining as much as 4 data, (3) expressive speech act function of blaming as much as 5 data, (4) expressive speech act function of praising as much as 3 data, (5) expressive speech act function of insinuating as much as 1 data, (6) the expressive speech act function of forgiving as much as 3 data, (7) the expressive speech act function of forgiving as much as 1 data, (8) the expressive speech act function of mocking as much as 6 and on the expressive speech act function of gratitude and congratulations are not found in the Kick andy Edition K. H. Abdurahman Wahid so that the amount of data is 27 data.